The Triple Combination Phentermine Plus 5-HTP/Carbidopa Leads to Greater Weight Loss, With Fewer Psychomotor Side Effects Than Each Drug Alone - Perez, Claudia I.; Kalyanasundar, B.; Moreno, Mario G.; Gutierrez, Ranier (Frontiers in Pharmacology, 2019)
Obesity has become a serious public health problem. Although diet, surgery, and exercise are the primary treatments for obesity, these activities are often supplemented using appetite suppressants. Hendricks et al., 2009 reported that obesity specialists frequently prescribed a new drug combination for its treatment that includes phentermine (Phen; dopaminergic appetite suppressant), a serotonin (5-HT) precursor 5-hydroxytryptophan (5-HTP; an appetite suppressant that increases the 5-HT concentration), and carbidopa (CB; peripheral blocker of conversion of 5-HTP to 5-HT). Despite its widespread use, there is neither a preclinical study confirming the drug efficacy nor studies of its effects on the brain. To fill this gap, in rats for 7 consecutive days we administered Phen intraperitoneally at different doses either alone or in combination with a fixed dose of 5-HTP/CB. In a different group, we infused drugs via an intraperitoneal catheter while extracellular-recordings were performed in the Nucleus Accumbens Shell (NAcSh), a brain region with dopamine-releasing effects that is involved in the action of appetite suppressants. We found that the triple-drug combination leads to greater weight-loss than each drug alone. Moreover, and as the treatment progresses, the triple drug combination partially reversed psychomotor side-effects induced by Phen. Electrophysiological results revealed that Phen alone evoked a net inhibitory imbalance in NAcSh population activity that correlated with the onset of psychomotor effects. In addition, and unlike the greater weight loss, the addition of 5-HTP/CB did not alter the Phen-evoked inhibitory imbalance in NAcSh responses. Subsequent experiments shed light on the underlying mechanism. That is the majority of NAcSh neurons modulated by 5-HTP/CB were suppressed by Phen. Notably, and despite acting via a different mechanism of action (DA for Phen vs. 5-HT for 5-HTP/CB), both drugs recruited largely overlapping NAcSh neuronal ensembles. These data suggest that the neural correlates of the greater weight loss could be located outside the NAcSh, in other brain circuits. Furthermore, we conclude that Phen + 5-HTP/CB is a potential treatment of overweight and obesity.